STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: STUDY OF INFORMATION TECHNOLOGY-BASED PAI LEARNING IN MADRASAH - Suwartiningsih Suwartiningsih (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2021)
Learning strategy is a process to achieve learning objectives in subjects. To achieve learning objectives, a long process is required starting with planning, organizing and assessing. To achieve the learning objectives, there are many kinds of information technology that can be used. Information technology as an educational medium is carried out using communication media such as telephone, computer, internet, e-mail, and so on. The problem of learning Islamic religious education (PAI) based on information technology is very urgent for in-depth research to be carried out in accordance with educational institutions in their learning processes that use various technological media in learning in madrasas. From the discussion in this writing, it is related to the concept of learning Islamic religious education based on information technology and applications in madrasas. At the end of writing the article is a closing which is a conclusion and at the same time provides suggestions or recommendations about learning Islamic religious education based on information technology in madrasas both theoretically and applicatively.